INTERNATIONAL EXPERIENCE IN MEASURING THE DIGITAL ECONOMY - Saida Khalil; Aykhan Ibrahimov (Agora International Journal of Economical Sciences (AIJES), 2023)
The article discusses the importance and challenges of measuring the digital economy. It evaluates the overall benefits of the GDP framework and introduces new concepts to define the digital economy as an object of measurement. The concepts used to define the digital economy as an object of measurement are the following. In order to quantify the benefits associated with the digital economy, a new metric is introduced to formally link it to traditional GDP and the concept of gross income is used as the main indicator to assess its economic impact on the regional economy. The main methodological approaches for constructing relevant indicators are described. The methodology for measuring the digital economy and the prospects for improving the knowledge base are identified.
Keywords: 330